The lived experiences of female Addicts in Emirati society - Al Balushi, Khadija; Al Hourani, Mohammed (Al-Adab Journal, 2026)
The current study aimed to reveal the lived experiences of female addiction to narcotic substances and Psychotropic Substances using the methodology of Dorothy Smith's feminist foresight point theory in collecting data, through in-depth interviews, which is a key pillar in the phenomenological perspective. The study focused on three main axes addressed first: factors and conditions leading to entry into addiction, second: incentives to seek treatment and rehabilitation, and finally: the current relationship with society.The sample of the study consisted of 24 drug addicts, interviewed in treatment and rehabilitation centers in the emirate of Dubai, represented by the Irada Center for treatment and rehabilitation and your help for social rehabilitation, penal and correctional institutions and the international protection center, and the results showed that the pre-addiction conditions were represented by the presence of self-motives such as deteriorating mental health or taking painkillers and some medical drugs to relieve pain or emptiness, weak parental control or the results also showed that the triggers for seeking treatment, some of which stem from  the addict herself, such as the desire for change, to the inability to interrupt communication between them and close family and friends, some of them sought treatment as a result of parental encouragement or transfer from one of the police centers. The results also showed that there is a disparity in the relationship with society among the respondents, as some of them see a lack of confidence in society and return to a normal life, while others believe that they are able to integrate into society and adapt to the new situation, with the skills and knowledge they have acquired.